A novel efficient bispecific antibody format, combining a conventional antigen-binding fragment with a single domain antibody, avoids potential heavy-light chain mis-pairing - Huang, Shuyu; Segues, Aina; Hulsik, David Lutje; Zaiss, Dietmar M.; Sijts, Alice J. A. M.; Van Duijnhoven, Sander M. J.; Van Elsas, Andrea (Journal of Immunological Methods, 2020)
Due to the technical innovations in generating bispecific antibodies (BsAbs) in recent years, BsAbs have become important reagents for diagnostic and therapeutic applications. However, the difficulty of producing a heterodimer consisting of two different arms with high yield and purity constituted a major limitation for their application in academic and clinical settings. Here, we describe a novel Fc-containing BsAb format (Fab × sdAb-Fc) composed of a conventional antigen-binding fragment (Fab), and a single domain antibody (sdAb), which avoids heavy-light chain mis-pairing during antibody assembly. In this study, the Fab x sdAb-Fc BsAbs were efficiently produced by three widely used heavy-heavy chain heterodimerization methods: Knobs-into-holes (KIH), Charge-pairs (CP) and controlled Fab-arm exchange (cFAE), respectively. The novel Fab x sdAb-Fc format provided a rapid and efficient strategy to generate BsAb with high purity and a unique possibility to further purify desired BsAbs from undesired antibodies based on molecular weight (MW). Compared to conventional BsAb formats, the advantages of Fab x sdAb-Fc format may thus provide a straightforward opportunity to apply bispecific antibody principles to research and development of novel targets and pathways in diseases such as cancer and autoimmunity.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Antibody chain association; Bispecific antibody; Charge-pairs; Controlled fab-arm exchange; Knobs-into-holes